Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1086/322451
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Independent Star Formation Diagnostics for an Ultraviolet‐selected Sample of Nearby Galaxies

Abstract: We present results from a decimetric radio survey undertaken with the Very Large Array (VLA) as part of a longer term goal to inter-compare star formation and dust extinction diagnostics, on a galaxy by galaxy basis, for a representative sample of nearby galaxies. For our survey field, Selected Area 57, star formation rates derived from 1.4 GHz luminosities are compared with earlier nebular emission line and ultraviolet (UV) continuum diagnostics. We find broad correlations, over several decades in luminosity,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
179
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(215 citation statements)
references
References 36 publications
(51 reference statements)
33
179
2
Order By: Relevance
“…Interestingly, all the galaxies at higher redshift (z $ 0:8) exhibit underestimated SFR UV . These results are consistent with the work of Sullivan et al (2001), who found that the UV/H ratio decreases with increasing SFR for galaxies in the redshift range 0 < z < 0:5, whereas for low-SFR objects the UV luminosities lead to higher SFRs than H . Previous observations of distant galaxies, using uncorrected H fluxes, had already revealed that the UV flux underestimates the SFR by a factor of a few (Glazebrook et al 1999;Yan et al 1999;Moorwood et al 2000).…”
Section: Sfr Uv and Sfr Hsupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, all the galaxies at higher redshift (z $ 0:8) exhibit underestimated SFR UV . These results are consistent with the work of Sullivan et al (2001), who found that the UV/H ratio decreases with increasing SFR for galaxies in the redshift range 0 < z < 0:5, whereas for low-SFR objects the UV luminosities lead to higher SFRs than H . Previous observations of distant galaxies, using uncorrected H fluxes, had already revealed that the UV flux underestimates the SFR by a factor of a few (Glazebrook et al 1999;Yan et al 1999;Moorwood et al 2000).…”
Section: Sfr Uv and Sfr Hsupporting
confidence: 93%
“…As a result of the advent of the Hubble Space Telescope (HST) and of the 8-10 m class telescopes, the rest-frame ultraviolet (UV) star formation history per unit comoving volume initially derived up to z $ 1 (Lilly et al 1996) was extended up to z $ 4 (Madau et al 1996;Steidel et al 1999). Naturally, all these works rely on the use of the available star formation rate (SFR) diagnostics: nebular emission lines like H (Kennicutt 1992a(Kennicutt , 1998Gallego et al 1995;Tresse & Maddox 1998;Glazebrook et al 1999;Moorwood et al 2000;Hopkins, Connolly, & Szalay 2000) and [O ii] (Hogg et al 1998;Aragó n-Salamanca et al 2002), UV continuum luminosities (Lilly et al 1996;Madau et al 1996;Treyer et al 1998;Cowie, Songalia, & Barger 1999;Steidel et al 1999;Sullivan et al 2000Sullivan et al , 2001, far-infrared (FIR) luminosities (Rowan-Robinson et al 1997;Blain et al 1999;Flores et al 1999;Chary & Elbaz 2001), and 1.4 GHz radio luminosities (Condon 1992;Cram et al 1998). Different cosmic star formation histories have been advocated from these various studies, which can only be reconciled if the effect of dust extinction is accounted for.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only spatially resolved studies would allow to remove this uncertainty. Hopkins et al (2001) and Sullivan et al (2001) report a positive correlation between the dust extinction traced by the Balmer decrement and the star formation rate of the galaxies traced by their total FIR or Hα luminosities. In Fig.…”
Section: The Extinction In the Hα Emission Linementioning
confidence: 96%